Serotype Variations and Distributions of Dengue Virus During the 2022 Outbreak in Chattogram, Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction: In the year 2022, a Dengue virus outbreak occurred nationwide in Bangladesh, including Chattogram, a port city. The purpose of this study was to identify and document the serotypes of Dengue virus and to measure the viral load of the virus positive specimens.Methods: This observational study was conducted in a tertiary care hospital of Chattogram during a period of six months from June through December, 2022. A total of 74 patients with symptoms suggestive of Dengue Fever(DF) and NS1 or IgM/IgG positive dengue patients were recruited into the study. From them clinicopathological data was collected on a case record form(CRF). Ten ml of venous whole blood was drawn in EDTA tubes then centrifuged and was sent to the laboratory at SlieaGen L.L.C in Austin, Texas, USA, for Dengue serotyping and viral load analysis by qPCR-LDT method. A total of 73 specimens were analyzed, one specimen was excluded. Ethical clearance was obtained from the hospital ethical review board, written informed consents were also taken from all subjects. Serotyping and qPCR testing data was shared by SlieaGen LLC once analysis was completed.Results: Amongst the 74 patients most were male 57(77%) and most [20(40.5%)] patients were young at 21-30 years. All had history of fever(100%), followed by body aches 67(90.5%), headache 49(66.2%) and weakness 55(74.3%). Positive NS1, IgM Dengue Ab and IgG Dengue Ab were found in 68(91.9%), 8(10.8%) and 3(4.1%) cases respectively. Frequency of serotype distributions revealed DENV 1 and DENV 3 were the most common serotypes 25(33.8%) and 16(21.6%) respectively also DENV 2 was 3(4.1%) and DENV 4 was 1(1.4%). Among 27 virus positive cases single infection DENV 1 was found in 10(13.51%) samples, DENV 3 and DENV 4 found in 1(1.4%) samples each, doubly infected (DENV 1 + DENV 2) was found in 12(16.2%) samples, triple infected (DENV 1 + DENV 2 + DENV 3) was found in 3(4.1%) samples. No virus was detected in 46(62.16%) samples. Viral load (Mean ± SD ) found in DENV 1(890974.48 ± 4156206)cp/ml, DENV 2 (33423.00 ± 9088.35)cp/ml, DENV 3(23991.12 ± 51250.18)cp/ml and DENV 4 (822.00cp/ml) in virus detected samplesConclusions: All four serotypes were found in the 2022 Dengue outbreak in Chittagong and DENV 1 and DENV 3 were common serotype. Simultaneous double and triple serotype infection in the same patients may be related with different unusual clinical features which need further documentations in future.J Bangladesh Coll Phys Surg 2023; 41: 39-43